Performance of 25 m Rope Trawl in Inshore Waters - S.V.S., Rama Rao; G., Narayanappa (Fishery Technology, 2025)
Rope trawl in which the leading sections of netting are substituted by ropes of sufficient breaking strength, is a recent innovation in trawl design. Design details of a 25 m rope trawl (200 mm x 320 meshes) developed for inshore trawling and its performance in the waters off Kakinada, Andhra Pradesh, India, are reported in this paper. The rope trawl appeared to be effective for capute of ribbonfish, silver bellies, anchovies, sciaenids and pomfrets. During comparative operations with a 25 m bulged belly trawl as control, the rope trawl registered a significantly (p< 0.01) low fuel consumption rate.